Community & Facility-based Study on Estimation of Out-of-Pocket Expenditure (OOPE): A Cross-sectional Analytical Study from Western India (GAIMS Journal of Medical Sciences, 2023)
Introduction: Janani Shishu Suraksha Karyakram (JSSK) is a key program for increasing the institutional delivery. This program is a boon for pregnant women who still deliver at home as well as for sick neonates who die on account of poor access to health facilities. Thus, current cross sectional analytical study was conducted to assess any Out-of-pocket expenditure (OOPE) by beneficiaries of JSSK.Methodology: 400 rural & urban beneficiaries of JSSK were enrolled from western part of India. Informed consent was sought & data about demographic profile, JSSK utilization & OOPE was collected in pre tested semi structured proforma.Results: Mean age of the beneficiaries was 24.87 years. 29.25% had to pay money availing the services. Most of the OOPE was for drugs & consumables. Age, age at marriage, religion, place of delivery, family size, having RSBY card, type of delivery, parity were predictors of OOPE among JSSK beneficiaries.Conclusions: Approximately 70% of beneficiaries received support through JSSK, yet around 30% still incurred expenses for healthcare services, highlighting the financial challenges faced.